Analysis Of Cybersecurity Issues In Social Networks - Abdullayev, Murodjon; O‘rinkulov, Odil (TLEP – International Journal of Multidiscipline, 2025)
This article analyzes the current problems of cybersecurity in social networks, their impact on society, users, and information security. In particular, risk factors such as fake accounts, phishing attacks, the spread of malware, and illegal collection and distribution of personal data are studied. Special attention is also paid to the cybersecurity culture that is being formed in the minds of users when using social networks. The article provides an analytical approach based on international experience, statistical data, and modern protective measures. As a result, proposals are put forward for the development of effective security strategies for users and responsible organizations.